How Do Therapists Understand and Intend to Implement Practice Guideline Recommendations for Rehabilitation of the Upper Limb Following Stroke? - Sahely, Ahmad (My University, 2017)
Stroke rehabilitation interventions must be evidence-based and applicable to a range of stroke subtypes and severity of disabilities to obtain the optimal outcomes. Clinical practice guidelines assist clinicians to implement rehabilitation plans based on research evidence. Evaluations of clinicians’ practices suggest that therapists may not be following guidelines, which may explain why patient outcomes are less than expected. To increase therapists' adherence to guidelines, it would help to understand their understanding, barriers and facilitators to implementing a clinical guideline. The purpose of this thesis was to demonstrate how rehabilitation therapists understand and interpret specific clinical guideline recommendations for upper limb rehabilitation post-stroke, and to identify perceived implementation barriers and facilitators. This thesis has two elements. The first demonstrates the application of the Theory of Planned Behaviour as a conceptual framework for understanding rehabilitation professionals’ intention toward implementation of clinical guidelines in rehabilitation of persons following stroke. The second part illustrates how physiotherapists and occupational therapists understand the individual recommendations for rehabilitation of upper extremity after stroke from the Canadian Best Practice Recommendations for Stroke Care. It also characterizes the barriers and facilitators that influence therapists’ uptake of these recommendations. The data for second manuscript were collected from therapists in two different countries (Canada and Saudi Arabia) to explore the global issues of clinical guidelines implementation. The review of the Theory of Planned Behaviour informed the study design and thinking about barriers and facilitators; but thematic analyses were driven by the data, not by theory. The similarities across health systems in the two countries were more striking than the differences, highlighting common challenges for guideline implementation. The findings of this thesis highlight the need for clearer communication of the specific actions intended by the CPG, and education of therapists to ensure they know how to implement interventions utilizing these specific actions.